Evidence of niche partitioning under ontogenetic influences among three morphologically similar siluriformes in small subtropical streams - Bonato, Karine Orlandi (2014)
Ontogenetic influences in patterns of niche breadth and feeding overlap were investigated in three species of Siluriformes (Heptapterus sp., Rhamdia quelen and Trichomycterus poikilos) aiming at understanding the species coexistence. Samplings were conducted bimonthly by electrofishing technique from June/2012 to June/2013 in ten streams of the northwestern state of Rio Grande do Sul, Brazil. The stomach contents of 1,948 individuals were analyzed by volumetric method, with 59 food items identified. In general Heptapterus sp. consumed a high proportion of Aegla sp., terrestrial plant remains and Megaloptera; R. quelen consumed fish, and Oligochaeta, followed by Aegla sp.; while the diet of T. poikilos was based on Simuliidae, Ephemeroptera and Trichoptera. Specie segregation was observed in the NMDS. Through PERMANOVA analysis feeding differences among species, and between a combination of species plus size classes were observed. IndVal showed which items were indicators of these differences. Niche breadth values were high for all species. The niche breadth values were low only for the larger size of R. quelen and Heptapterus sp. while T. poikilos values were more similar. Overall the species were a low feeding overlap values. The higher frequency of high feeding overlap was observed for interaction between Heptapterus sp. and T. poikilos. The null model confirmed the niche partitioning between the species. The higher frequency of high and intermediate feeding overlap values were reported to smaller size classes. The null model showed resource sharing between the species/size class. Therefore, overall species showed a resource partitioning because of the use of occasional items. However, these species share resources mainly in the early ontogenetic stages until the emphasized change of morphological characteristics leading to trophic niche expansion and the apparent segregation observed.